Pengaruh Kompleksitas Tugas dan Kompetensi Audit Terhadap Kualitas Audit dengan Integritas Auditor sebagai Variabel Moderating - Khalisah Visiana Subekti (Universitas 17 Agustus 1945 Jakarta, 2023)
This article proves the influence of the Influence of Task Complexity and Audit Competence on Audit Quality moderated by Auditor Integrity. The results tested, the effect of Task Complexity and Audit Competence on Audit Quality with Auditor Integrity as Moderating Variable. The research population is all Auditors of Public Accounting Firms in Jakarta City with a total of 100 auditors as research samples. The quality of audits is still widely questioned by the public because there are still various public assessments in assessing public accounting firms, this assessment can be measured from the competence of the auditors who are the spearhead in the audit process. In addition to issues related to auditor competence, the same thing with integrity and ethics of auditors is one of the factors to determine the audit quality of public accounting firms. This study aims to assess the effect of auditor competence, integrity and auditor ethics on audit quality. The analysis uses Structural Equation Modelling to test this research model. Next, examine the effect of the Effect of Task Complexity and Audit Competency Education on Audit Quality moderated by Auditor Integrity.